Examining the relationship between farmer participation in an agri-environment scheme and the quantity and quality of semi-natural habitats on Irish farms. (September 2022) - Tsakiridis, Andreas; O'Donoghue, Cathal; Ryan, Mary; Cullen, Paula; Ó hUallacháin, Daire; Sheridan, Helen; Stout, Jane
Abstract: Agri-environment schemes (AESs) have been developed by governments to improve biodiversity, reduce pollution from farming and encourage the provision of agriculture's non-market benefits. Despite the substantial amount of money spent on designing, implementing and monitoring AESs, their environmental effectiveness is ambiguous. The objective of this paper is to investigate the relationship between farmer participation in an AES and the quantity and quality of semi-natural habitats found on farms. This study combines socio-economic survey data from Irish farms in 2012 with farmland habitat data collected in 2015–16 from a subset of participating farms in the original 2012 socio-economic survey. Given the voluntary nature of AESs, a matching technique is applied to control for self-selection bias and test whether farmer participation in an AES is related to the quantity and quality of habitats found on Irish farms. Although farmer participation in an AES is found to be positively related to habitat quantity and quality, we are unable to reject the null hypothesis of no statistically significant differences between habitat quantity and quality of participants in an AES and non-participants. However, results highlight that the share of habitat area (proxy variable for habitat quantity) varies significantly across farm households with different socio-economic characteristics, soil type, farm structures and location. Future policies could scale up the implementation of outcome-based payments or market-based instruments to incentivize farmers in improving their environmental performance. However, such policy improvements would still require the development of robust and transparent monitoring mechanisms. Highlights: Participation in an AES is positively related to habitat quantity and quality. However, these relationships are statistically non-significant. The share of habitat area varies across farm households with different socio-economic characteristics, soil type, farm structure and location. Policies could scale up the implementation of results-based payments to incentivize farmers in improving their environmental performance.